KEBIJAKAN PEMEKARAN KECAMATAN DAN PELAYANAN MASYARAKAT - Amir, Amir; Sujianto, Sujianto; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2018)
Policies of District Expansion and Community Service. This study aims to determine the efforts of the policy of accelerating the expansion of the districts and to determine what factors are related to the policy of the expansion of the districts. The type of research is a qualitative approach. The research informants were 12 people taken by the Chairman and Members of DPRD, Chairman and Members of BPD, Bureau of Government, Sekcam, Village Head and Community Leader. Data collection techniques that the author did with observation, Documentation, and interviews. Analysis of data that the authors used in this study is an interactive analysis model. The results of the research show that the district of Bantan has not been bloomed because there has been no proposal about the pemekaran from the village of Bantan kecmatan. Bantan sub-district inhibiting factors are not established ie no good communication exists between the village and sub-district, as well as communication between the regional head and the regional parliament on the expansion of the districts. In terms of resources, there is no expert to conduct an assessment of sub-district pemekaran. As for the disposition they agreed but none became the implementor of the policy of the expansion of the districts. Furthermore, about the bureaucracy in doubt of the new law, namely Law No. 23 of 2014 on local government has not replaced government regulation No. 19 of 2008 on the district.